Regional Hegemony in the Periphery: A Study of Nigeria - Talibu Oladimeji (Journal of Diplomacy and International Studies, 2021)
The article examines Nigeriaâ€™s place in international political system in relation to the concept of hegemony. It seeks to assess the scholarly claim of Nigeria as a regional hegemon in Africa. The unclear classification of some countries in the global political system and the function such states could play in promoting peace and stability has not received expected attention of international relation scholars. This does not come as a surprise as the discipline itself is rooted in American and European diplomatic practice. As such, it is necessary to provide tentative, if not permanent, designation for state like Nigeria in the contemporary global system. It is conventional in the history of international relations to ascribe all changes in the global politics to the influence of superpowers or great powers. The role of other actors, most especially in relation to Nigeria, is not properly examined and this has resulted in what can be termed as â€œidentity crisisâ€. In order to provide designation for the role Nigeria plays in global politics, it is important to engage in some sort of empirical analysis. Thus, the article examines the extent to which Nigeria can be designated as regional hegemon in Africa. In conducting this research, process tracing, discourse analysis and latent content analysis are utilized in analyzing documents, interview transcripts, and existing published works.